Expression of vascular endothelial growth receptors in human papilloma virus-related oral squamous cell carcinoma cell lines - Aziz, Muhammad Zulhilmi Ab (2024)
Oral squamous cell carcinoma (OSCC) is the most common type of malignancy that arises from mucosal epithelial lining of oral cavity. Smoking tobacco, alcohol consumption and Human Papillomavirus (HPV) are the main risk factors for OSCC. However, the effect of HPV infection in OSCC towards Vascular Endothelial Growth Factor Receptor (VEGFR) signalling in OSCC development is still unclear. This study aims to determine the expression of VEGFR1, VEGFR2, phosphorylated VEGFR1 (pVEGFR1), phosphorylated VEGFR2 (pVEGFR2) and Ki-67 with regards to HPV status in OSCC cell lines. Two types of OSCC cell lines which are HSC-2 (HPV-negative) and UPCI:SCC154 (HPV-positive) were maintained according to their recommended conditions. The expression of VEGFR1, VEGFR2, pVEGFR1, pVEGFR2 and Ki-67 were analysed using flow cytometry. The expression of VEGFR2 and pVEGFR2 were significantly higher on HSC-2 cells while significantly higher expression of Ki-67 was shown on SCC154 cells. Nevertheless, the protein expression value for all the targeted markers was higher on HSC-2 cells but not for Ki-67 which was higher on SCC154 cells. As conclusion, this study revealed that HPV infection in OSCC decreased the VEGFR expression which resulted in lower angiogenesis activity in HPV-infected OSCC. High Ki-67 expression in HPV-infected OSCC suggested that cell proliferation activity in HPV-infected OSCC was high even though lower angiogenesis marker were presented.